Financial Literacy and Use of Fintech in MSMEs: Systematic Literature Analysis - Tullaili, Mufida; Susanto, Perengki (Indonesian Journal Publisher, 2025)
This research aims to evaluate the influence of financial literacy and the use of fintech on the performance of MSMEs. Using a systematic literature review method, researchers identified and analyzed various relevant studies to understand how financial literacy and fintech influence the development and operational efficiency of MSMEs. The review results show that good financial literacy enables MSMEs to understand and use fintech services effectively, which in turn increases access to financing and optimizes financial management. Meanwhile, fintech offers more flexible and inclusive financial solutions, which contribute significantly to increasing financial inclusion and the growth of MSMEs. The combination of adequate financial literacy and the appropriate use of fintech has been proven to have a positive impact on the performance and competitiveness of MSMEs. Based on these findings, the research recommends increasing financial literacy programs and wider integration of fintech services to support the development of MSMEs in Indonesia, as well as increasing financial inclusion for the wider community